2008
DOI: 10.1136/gut.2007.135053
|View full text |Cite
|
Sign up to set email alerts
|

IL23 differentially regulates the Th1/Th17 balance in ulcerative colitis and Crohn's disease

Abstract: IL23 may play important roles in controlling the differential Th1/Th17 balance in both UC and CD, although Th17 cells may exist in both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
333
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(372 citation statements)
references
References 47 publications
23
333
4
5
Order By: Relevance
“…Furthermore, genetic RORγ deficiency of T cells pre vented T cell transfer of colitis in RAG knockout mice 84 . As RORA and RORC proteins, as well as T H 17 cytokines, are augmented in patients with IBD 121,122 , these data suggested that targeting of ROR proteins might be useful in these patients. Moreover, both genetic and pharmacological (via DNAzyme) blockade of GATA3, a key transcription factor for T H 2 cytokine gene tran scription, ameliorated chronic oxazolone mediated and TNBS (2,4,6 trinitrobenzenesulfonic acid) mediated colitis in mice 119 .…”
Section: T Cellmentioning
confidence: 94%
“…Furthermore, genetic RORγ deficiency of T cells pre vented T cell transfer of colitis in RAG knockout mice 84 . As RORA and RORC proteins, as well as T H 17 cytokines, are augmented in patients with IBD 121,122 , these data suggested that targeting of ROR proteins might be useful in these patients. Moreover, both genetic and pharmacological (via DNAzyme) blockade of GATA3, a key transcription factor for T H 2 cytokine gene tran scription, ameliorated chronic oxazolone mediated and TNBS (2,4,6 trinitrobenzenesulfonic acid) mediated colitis in mice 119 .…”
Section: T Cellmentioning
confidence: 94%
“…This suggests that C3 biosynthesis may be dependent upon molecular mechanisms specific and non-specific for IBD, as complements are major factors in innate immune responses against a huge number of antigens. An increasing number of studies have focused upon the role of Th17 cells in the pathogenesis of IBD [8,10,[12][13][14]47], due to its unique differentiation processes under the stimulus of transforming growth factor (TGF)-b and IL-6 [3][4][5][6][7][8][9][10][11]. Th17 cells develop from naive T lymphocytes through distinct pathways from classical Th1 and Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies focused upon a critical role of T helper type 17 (Th17) cells and interleukin (IL)-17 in the pathogenesis of IBD [3][4][5][6][7][8][9][10][11]. Th17 cells are novel subsets of CD4 + T cells, characterized by IL-17 secretion and the expression of the transcription factor retinoic acid-related orphan receptor (ROR)g [8,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, aggravation of clinical symptoms in GFAP-Cre FasL fl/fl mice correlated with an increased IL-17 mRNA transcription, indicating that this cytokine was decisive for the more severe and persisting EAE in these mice. IL-23, which drives IL-17 polarization of CD4 + T cells was not increased in the CNS of GFAP-Cre FasL fl/fl mice, which fits to the important role of IL-23 for Th17 polarization in lymphatic organs [31].…”
Section: Discussionmentioning
confidence: 88%
“…Thus, aggravation of clinical symptoms in GFAP-Cre FasL fl/fl mice correlated with an increased IL-17 mRNA transcription, indicating that this cytokine was decisive for the more severe and persisting EAE in these mice. IL-23, which drives IL-17 polarization of CD4 + T cells was not increased in the CNS of GFAP-Cre FasL fl/fl mice, which fits to the important role of IL-23 for Th17 polarization in lymphatic organs [31].Astrocytes play both positive and negative roles in the pathogenesis and development of EAE [32]. As part of the blood-brain barrier, early chemokine release of astrocytes contributes to the recruitment of autoimmune CD4 + T cells to the CNS [33].…”
mentioning
confidence: 91%